Discurso informativo audiovisual: sentidos engendrados na enunciação telejornalística - Torres, Carla Simone Doyle (2008)
Brazil, everyday in our houses, represented by a language that conjugates the power of speech of authority instituted to the nearly undisputed power of images. But how are these printed truths produced and sustained in each new edition of a nationwide television newscast? In order to clarify fundamental aspects of textual strategies which show a relation of enunciative instance with the audiovisual informative texts, as well as the resulting effects of this manipulation, theoreticalmethodological categories based on the detailing of the effects of enunciation and reality were elected. The theoretical-methodological contribution includes authors such as Foucault, Charaudeau, Verón, Vilches, Mouillaud, Maingueneau, Peruzzolo, Fausto Neto, Duarte and Becker. Allied to the theoretical categories, we also have, duly detailed, the empirical journalistic structures present in the corpus formed by editions of Jornal da Band and Jornal Nacional. The objective is to detect the circulating senses in two of the most important television newscasts of the country. Without any intention of comparison between the referred informative products, this characteristic collaborates as a methodological tool for observation of the possible diversity of angulations and speech data treatments of daily life under the media holophotes. Among the main results is the most frequent subjective enunciative deepening in Jornal da Band, as well as a more pronounced tendency to the objectification of the informative texts.